ANALYSIS OF CONTENT AND LANGUAGE INTEGRATED LEARNING METHODOLOGY IN THE VOCABULARY LEARNING PROCESS AT FIRST OF BACCALAUREATE CLASS ¨A¨ IN THE UNIDAD EDUCATIVA PCEI DE FORMACIÓN ARTESANAL ¨CRUZADA SOCIAL¨ FROM RIOBAMBA CITY, DURING THE ACADEMIC YEAR 2018-2019. - Cabrera Rivadeneyra, Katheryn Jhomira (2019)
Content and Language Integrated Learning (CLIL) is one of the most important methodologies, which embraces academic content and language proficiency. In Ecuador, CLIL methodology must be used since it is stated in the National Curriculum Guidelines (2016). Therefore, teachers are in charge of applying CLIL in order to give students the opportunity use the English language in different fields and situations. Despite of this statement, through a previous analysis it was determined as a problem that CLIL is not enhancing the vocabulary development in dressmaking students from Unidad Educativa Pcei De Formación Artesanal ¨Cruzada Social¨. According to their specialization all the subjects are related to tailoring, however, the contents and vocabulary taught in English class do not fit with students’ needs and interest. Hence, this study focuses on analyzing the Content and Language Integrated Learning Methodology in the Vocabulary Learning Process in Unidad Educativa Pcei De Formación Artesanal “Cruzada Social”. In order to achieve the established objectives, one English teacher and fifteen students from First Year of Baccalaureate “A” were taken as a population. The type of the developed study is qualitative with an exploratory level; while, the qualitative method employed was ethnographic. Furthermore, the observation technique was used and an observation sheet was applied in order to collect the needed information. The research results are shown by a descriptive analysis of the importance, process and effectiveness of CLIL methodology in the vocabulary development.